Implementasi Akad Hybrid Contract (Multi Akad) Murabahah Bil Kafalah Di BMT Tanjung: Analisis Kesesuaian terhadap Fatwa DSN-MUI dan Prinsip Fikih Muamalah - Rofiatus Zahro; Achmad Febrianto (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
Implementation of hybrid contracts in Islamic microfinance institutions continues to develop as an adaptive financing model capable of accommodating community needs while maintaining compliance with sharia principles. The practice of murabahah bil kafalah financing at BMT Tanjung reflects the integration of sale and guarantee contracts designed to provide safer and more accessible financing, particularly for micro, small, and medium enterprises (MSMEs). This research employed a qualitative case study approach through observation, semi-structured interviews, documentation, and questionnaires involving BMT managers, staff, and customers. Data were analyzed using data reduction, presentation, and verification techniques supported by source triangulation. The findings indicate that the implementation of murabahah bil kafalah generally aligns with DSN-MUI fatwas and fiqh muamalah principles, particularly regarding transparency of margin, determination of principal prices, and the role of kafalah as financing security. The existence of guarantors contributes to reducing financing risks and maintaining institutional profitability stability. Nevertheless, several operational challenges remain, including limited customer understanding of hybrid contracts, insufficient transparency regarding administrative costs, and differences in interpretation among operational staff. Strengthening contract transparency, improving staff competency, and enhancing customer education are necessary to optimize sharia compliance and increase public trust in hybrid financing practices within Islamic microfinance institutions.